Optimasi Kadar Maleat Anhidrat Dan Suhu Pada Pembuatan Maleated Natural Rubber Melalui Proses Grafting - Yunus, Aulia; Yelmida, Yelmida; Bahruddin, Bahruddin (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Natural rubber can be developed through a process called Maleated Natural Rubber grafting. A study about the influence of the composition of maleic anhydric (MAH) and temperature on the degree of grafting has been done before. The purpose of this research is to determine the optimum composition and temperature in the process of MAH grafted natural rubber. The composition of MAH is 7, 8, 9, and 10 phr with temperature conditions is 150, 155, 160 and 165oC. The grafting process use internal mixer operated at 60 rpm for 10 minutes. Grafting degree determined by titrimetric method where MNR in xylene solution titrated using MeOH solution. The results showed that the optimum composition and the temperature are 8.36 phr and 160oC with 3.62% grafitng degree. Keywords: grafting degree, maleic anhydric, maleated natural rubber, optimation, temperatur